x+7x-12=14-3x+1

Simple and best practice solution for x+7x-12=14-3x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+7x-12=14-3x+1 equation:


Simplifying
x + 7x + -12 = 14 + -3x + 1

Reorder the terms:
-12 + x + 7x = 14 + -3x + 1

Combine like terms: x + 7x = 8x
-12 + 8x = 14 + -3x + 1

Reorder the terms:
-12 + 8x = 14 + 1 + -3x

Combine like terms: 14 + 1 = 15
-12 + 8x = 15 + -3x

Solving
-12 + 8x = 15 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-12 + 8x + 3x = 15 + -3x + 3x

Combine like terms: 8x + 3x = 11x
-12 + 11x = 15 + -3x + 3x

Combine like terms: -3x + 3x = 0
-12 + 11x = 15 + 0
-12 + 11x = 15

Add '12' to each side of the equation.
-12 + 12 + 11x = 15 + 12

Combine like terms: -12 + 12 = 0
0 + 11x = 15 + 12
11x = 15 + 12

Combine like terms: 15 + 12 = 27
11x = 27

Divide each side by '11'.
x = 2.454545455

Simplifying
x = 2.454545455

See similar equations:

| 27x^2y^3+x^3y= | | -4(k-10)=-28 | | u/6{{^7/9}} | | TC=20+4Q | | 144-81x^2= | | b-7/14=-1 | | x^2-53x=144 | | -40=5(x+9) | | r/8-9=-10 | | (4f+5)+(5+40)=180 | | 0.025(4m-3)=0.05(10m-9) | | 0.02(4m-3)=0.05(10m-9) | | -2=-6-x | | 3(0)+5y-4=-18 | | 37+8x=4 | | 4y=1x+8 | | y=hx | | x^2-56x+96=0 | | x^2-53x=288 | | 1=a-7/4 | | 9rg^4-9rk^4=0 | | x^2-53x=222 | | -5(2+2x)-3x=-62 | | -95=5(-7+a) | | (n+6n-4)(2n-4)= | | -4(3+5v)=-72 | | 88=8(7+m) | | 2g-(g-3)= | | (7r-6r-6)(2r-4)= | | 0.02(9c-84)=-0.6(c-5) | | -5(2r+5)=-65 | | p+6=0 |

Equations solver categories